An improved lower bound of genuine tripartite entanglement concurrence. (22nd October 2021) - Wang, Jing; Zhu, Xuena; Li, Ming; Shen, Shuqian; Fei, Shao-Ming
Abstract: As one of the important types of entanglement, genuine multipartite entanglement (GME) offers significant advantages in many quantum information processing tasks. We study the GME concurrence and present an improved lower bound of the GME concurrence for tripartite systems, which is shown to be much tighter than some existing ones. We show by detailed example that our new bound can detect more genuine tripartite entangled states. While it is a formidable task to compute the genuine tripartite entanglement concurrence analytically, our results give an effective operational way to estimate the genuine tripartite entanglement.